Effects of Trichilia monadelpha (Thonn.) J. J. De Wilde (MELIACEAE) Bark Extracts on Ulcerative Colitis, Colonic Microflora and Wound Healing in Wistar Rats - Ayande, Patrick George (2012)
A Thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the Degree of Master of Philosophy in Pharmacology, March-2011